Medieval Settlement “Samar”: on the Issue of Analysis and Interpretation of Sources - Galimov Sh.Kh. (Zolotoordynskoe Obozrenie, 2024)
The purpose of the study: To analyze well-known materials and introduce published sources and works of researchers into a wide scientific circulation, indicating the possibility of the appearance of Samara in the Golden Horde era. Research materials: “Nogai affairs”. “Piskarevsky Chronicler”, the works of domestic and foreign researchers of the 19th century and the post-revolutionary period. Results and scientific novelty of the study: According to the current historiographical theory, the time and circumstances of the emergence of the town (fortress) of Samara are defined as being in 1586 and are associated with the construction of a new Russian fortress in the tract at the confluence of the Samara and Volga rivers on the southeastern borders of the Moscow state. In establishing and recognizing this fact by the main part of researchers (and especially in the practice of promoting historical knowledge), a certain mythologization of the event played an important role when, as is found in well-known historical documents, a settlement with the same name was founded in the middle of the 14th century in the area of the current city of Samara. In most scientific and popular scientific publications, sources that could contribute to a more comprehensive and objective disclosure of the topic are rejected without sufficient argumentation. Therefore, official historiography continues to adhere to the point of view that, firstly, the well-known maps of Pizigani in 1367 and Fra Mauro in 1459 incorrectly reflect the geography of Eastern Europe and, secondly, if the said settlement of Samar existed at that time, it cannot be considered a forerunner of the current city of Samara. Meanwhile, historical documents and a detailed analysis of the works of researchers of the 19th century with their complex use, at least, allow us to question these categorical statements and raise new questions about the events preceding the inclusion in the 16th century of the Middle Volga as part of the Russian state.